2018
DOI: 10.1186/s13568-018-0618-z
|View full text |Cite
|
Sign up to set email alerts
|

An alkaline and surfactant-tolerant lipase from Trichoderma lentiforme ACCC30425 with high application potential in the detergent industry

Abstract: Alkaline lipases with adaptability to low temperatures and strong surfactant tolerance are favorable for application in the detergent industry. In the present study, a lipase-encoding gene, TllipA, was cloned from Trichoderma lentiforme ACCC30425 and expressed in Pichia pastoris GS115. The purified recombinant TlLipA was found to have optimal activities at 50 °C and pH 9.5 and retain stable over the pH range of 6.0–10.0 and 40 °C and below. When using esters of different lengths as substrates, TlLipA showed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Recombinant lipase showed stability in the presence of reducing agents as well as inhibitors. These results are in accordance to previous studies (Alabdalall et al, 2021; Prazeres et al, 2006; Rathi et al, 2001; Shoja & Minai‐Tehrani, 2021; Wang et al, 2018). Stability of enzyme in organic solvents is a preferred characteristic for industrial utilization.…”
Section: Discussionsupporting
confidence: 93%
“…Recombinant lipase showed stability in the presence of reducing agents as well as inhibitors. These results are in accordance to previous studies (Alabdalall et al, 2021; Prazeres et al, 2006; Rathi et al, 2001; Shoja & Minai‐Tehrani, 2021; Wang et al, 2018). Stability of enzyme in organic solvents is a preferred characteristic for industrial utilization.…”
Section: Discussionsupporting
confidence: 93%
“…It is considered that surfactants have a negative effect on enzymatic hydrolysis and are a competitive inhibitor in the reaction system [ 40 ]. The influence of surfactants on the activity of enzymes, e.g., lipase, has been studied to date [ 41 ]. In this paper, the effect of surfactants on laccase stability in the laccase–exopolysaccharide system was tested for the first time in the presence of anionic surfactant 10% SDS and two non-ionic surfactants, i.e., Tween-80 and Triton X-100.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, a method was developed for constructing hybrid promoters harboring different copy numbers of the upstream activation sequences fragment (UAS1B), and the recombinant strain Po1g/hp12d-rml 25# reached 38.9 U/ml. Wang et al (2018) increased the 48.7% recombinant lipase activity of Galactomyces geotrichum in Pichia pastoris through codon optimization of the lipase gene.…”
Section: Molecular Techniques In Lipase Productionmentioning
confidence: 99%
“…Furthermore, these lipases, including Humicola lanuginosa, Talaromyces thermophilus, Rhizopus oryzae, and candida sp., are also used in the preparation of detergents that promise better washing performance and energy savings (Nishioka et al, 1990;Salleh et al, 1993;Jaeger et al, 1994;Romdhane et al, 2010;Mahfoudhi et al, 2022). Wang et al (2018) reported an alkaline, low-temperature, and strong surfactant tolerance recombinant lipase of Trichoderma lentiform ACCC30425 in Pichia pastoris GS115; this lipase is suitable for use in the detergent industry. Xiao et al (2021) also reported a recombinant lipase Lip486 without clear homology alao to know lipase, Lip486 was discovered by using functional metagenomics technology and belongs to a new sub-familycalled lipolytic enzyme family II.…”
Section: In Detergent Manufacturingmentioning
confidence: 99%